Economics of Regaining Office: The Case of Pakistan (1947-2005) (The Pakistan Development Review, 2006)
Political business cycle (PBC) can be defined as fluctuations in the economy due to an attempt of a government to manipulate the economy prior to elections for favourable outcomes i.e. regaining its office. The concept of policy cycles gained a good deal of attention by the economists during mid 70s. Though most of the researchers attribute the PBC theory to Schumpeter (1939) and Kalecki (1943) but the seminal work in the theory of PBC is Nordhaus (1975).